2010
DOI: 10.1209/0295-5075/91/56002
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing and coherent structure formation in organic-organic heterostructure growth

Abstract: We use in situ real-time X-ray reflectivity and complementary atomic force microscopy to monitor crystallinity and roughness evolution during growth of organic heterostructures, i.e. perfluoropentacene (PFP) on diindenoperylene (DIP) and pentacene (PEN) on PFP. For both systems, surface smoothing during thermal evaporation of the second material on top of the first is observed. The smoothing can be rationalized by a, compared to homoepitaxy, lowered step edge barrier for one species diffusing on the other. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
(44 reference statements)
2
24
0
Order By: Relevance
“…At 303 K, the non-equimolar mixtures, in particular, exhibit very pronounced oscillations, indicating very smooth films. This might be explained by C 60 filling the voids between the 6T domains or vice versa, similar to results for perfluoropentacene deposited on diindenoperylene or pentacene on perfluoropentacene, where a small step edge barrier leads to a smoothing of the bottom layer when an overlayer is deposited on top (Hinderhofer et al, 2010).…”
Section: Resultssupporting
confidence: 68%
“…At 303 K, the non-equimolar mixtures, in particular, exhibit very pronounced oscillations, indicating very smooth films. This might be explained by C 60 filling the voids between the 6T domains or vice versa, similar to results for perfluoropentacene deposited on diindenoperylene or pentacene on perfluoropentacene, where a small step edge barrier leads to a smoothing of the bottom layer when an overlayer is deposited on top (Hinderhofer et al, 2010).…”
Section: Resultssupporting
confidence: 68%
“…The suitability of measuring the x-ray reflectivity at the so called anti-Bragg point in reciprocal space to study layer-by-layer growth has been demonstrated for several organic systems. 18,[35][36][37][38][39] Layer interference leads to temporal oscillations of the reflected intensity during layer-by-layer growth. 39,40 This can be seen directly from the equation for the reflected intensity I reflected (t), as calculated in kinematic approximation…”
Section: Resultsmentioning
confidence: 99%
“…[79] For both systems, surface smoothing during thermal evaporation of the second material on top of the first is observed. The smoothing mechanism is sketched in Figure 3 a.…”
Section: Smoothing For A/b-type Heterostructuresmentioning
confidence: 91%
“…Another interesting effect is smoothing ( Figure 3), which was observed for growth of PFP on DIP and PEN on PFP. [79] For both systems, surface smoothing during thermal evaporation of the second material on top of the first is observed. The smoothing mechanism is sketched in Figure 3 a.…”
Section: Smoothing For A/b-type Heterostructuresmentioning
confidence: 91%